Pengaruh Return On Assets, Net Profit Margin, Earning Per Share, dan Debt To Equity Ratio Terhadap Return Saham - Salsabila, Salsabila; Suhaili, Achmad (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
This study aims to determine and analyze: (1) The effect of Return on Assets on Stock Return (2) The effect of Net Profit Margin on Stock Return (3) The effect of Earning Per Share on Stock Return and (4) The effect of Debt to Equity Ratio on Stock Return. The population LQ45 IDX period 2020. Number of samples amounted to 12 companies. Sampling technique used purposive sampling. The results of this study found that Return on Assets, Net Profit Margin, Earning Per Share, and Debt to Equity Ratio have no effect on Stock Return Non-Bank LQ45 Companies Listed on Indonesian Stock Exchange. The limitation of this study is that there are extreme data that makes the data not normally distributed, therefore it is necessary to do outliers, and the coefficient of determination (R2) is very low -0.050 where the results show that the independent variables tested in this test cannot determine returns. stock as a whole because there is something that is not explained in this test. Keywords: return on assets, net profit margin, earning per share